Enhancing food preservation with postbiotic metabolites c-aminobutyric acid (GABA) and bacteriocin-like inhibitory substances (BLIS) produced by Lactobacillus brevis C23 co-cultures in plant-based medium - Wei Wei Chuah; Joo Shun Tan; Siti Nur Hazwani Oslan; Pandian Bothi Raja (Taylor & Francis Online, 2023)
Lactic acid bacteria (LAB) can produce c-aminobutyric acid (GABA) with antioxidant properties and sedative effects when it binds to the GABA receptor in the human brain. LAB can also produce bacteriocin-like inhibitory substances (BLIS) with antimicrobial capabilities during carbohydrate fermentation. GABA and BLIS are natural compounds with potential health benefits and food preservation properties. Lactobacillus brevis C23 was co-cultured with three different LABs as inducers, which produced the highest GABA content and BLIS activity. They were cultured in various plantbased media to obtain an edible and better-tasting final product over commercially available media like MRS broth. A coconut-based medium with additives was optimized using response surface methodology (RSM) to increase GABA and BLIS production. The optimized medium for maximum GABA production (3.22 ± 0.01 mg/mL) and BLIS activity (84.40 ± 0.44%) was a 5.5% coconut medium containing 0.23% glucose, 1.44% Tween 20, 0.48% L-glutamic acid, and 0.02% pyridoxine. Due to the presence of GABA, the cell-free supernatant (CFS) as a postbiotic showed higher antioxidant activity than other food preservatives like nisin and potassium sorbate. Finally, microbiological tests on food samples showed that the postbiotic was more effective than other preservatives at combating the growth of LAB, molds and coliform bacteria, making it a possible food preservative.